2019
DOI: 10.3390/vetsci6040077
|View full text |Cite
|
Sign up to set email alerts
|

Sertoli Cell Tumor (SCT) in a Captive Black Bear (Ursus americanus)

Abstract: A black bear of 29-year-old (Ursus americanus) died unexpectedly in captivity without any gross lesions or clinical signs. We identified a firm, lobulated, yellowish tan, and well-circumscribed mass embedded inside the testicular tissue at the time of necropsy. The tumor sections exhibited soft necrotic and hemorrhagic areas beneath its capsule. Histologically, the tumor comprised Sertoli cells arranged in tubules and solid sheets supported by prominent fibrous connective tissues. The Sertoli cells were positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Testicular tumors were found in four bears, three of which were the oldest bears in the study (29–32 y/o), suggesting tumor development may be age related, consistent with reports of geriatric black bears and brown bears [ 35 , 36 ]. Unfortunately, the timing of the onset of tumor development cannot be determined.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Testicular tumors were found in four bears, three of which were the oldest bears in the study (29–32 y/o), suggesting tumor development may be age related, consistent with reports of geriatric black bears and brown bears [ 35 , 36 ]. Unfortunately, the timing of the onset of tumor development cannot be determined.…”
Section: Discussionsupporting
confidence: 89%
“…This male passed away five years following the successful October collection, and upon necropsy, it was revealed that there was a tumor within one of the testes. Testicular tumors have also been reported in both geriatric black bears [ 36 ] and brown bears [ 37 ]. Some types of testicular tumors in humans are associated with an increase in testosterone production [ 38 ].…”
Section: Discussionmentioning
confidence: 99%